Pengaruh Brand Image UMKM (Naila Cookies) terhadap Keputusan Pembelian Konsumen Guna Meningkatkan Produk - Nirmala, Yanti; Asri, Wulandari (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to determine the effect of brand image on consumer purchasing decisions for Naila Cookies products. Brand image is one of the key factors in shaping consumer perceptions of product quality and credibility. The research uses a quantitative associative approach with a total of 30 respondents who are consumers of Naila Cookies. Data were collected through questionnaires and analyzed using simple linear regression with SPSS version 26. The results show that brand image has a positive and significant effect on consumer purchasing decisions, with a regression coefficient value of 0.816 and a significance level of 0.000 (p < 0.05). The R Square value of 0.490 indicates that brand image explains 49% of the variation in purchasing decisions. These findings suggest that the better a product’s brand image, the higher the likelihood of consumer purchases. Therefore, MSMEs like Naila Cookies need to strengthen their brand image to increase customer loyalty and buying interest.